30.8k views
1 vote
PLEASE HELP!! what is the equation for the parabolic function that goes through the points (-3, 67) (-1, 1) and has a stretch factor of 9

2 Answers

0 votes
AEUJNDUOMBDWEIOOMXAIKMOOESVNOUEWDCYVUJOLDS
User Masanori
by
5.6k points
5 votes

Answer:


f(x)=9(x+(1)/(6))^2-(21)/(4)

Explanation:

So, we need to find the equation of a parabolic function that goes through the points (-3,67) and (-1,1) and has a stretch factor of 9.

In other words, we want to find a quadratic with a vertical stretch of 9 that goes through the points (-3,67) and (-1,1).

To do so, we first need to write some equations. Let's use the vertex form of the quadratic equation. The vertex form is:


f(x)=a(x-h)^2+k

Where a is the leading coefficient and (h,k) is the vertex.

Since a is the leading coefficient, it's also our stretch factor. Thus, let a equal 9.

Also, we have two points. We can interpret them as functions. In other words, (-3,67) means that f(-3) equals 67 and (-1,1) means that f(-1) equals 1. Write the two equations:


f(x)=a(x-h)^2+k\\f(-3)=67=9((-3)-h)^2+k

And:


f(x)=a(x-h)^2+k\\f(-1)=1=9((-1)-h)^2+k

Now, we essentially have a system of equations. Thus, to find the original equation, we just need to solve for the vertex. To do so, first isolate the k term in the second equation:


1=9(-1-h)^2+k\\k=1-9(-1-h)^2

Now, substitute this value to the first equation:


67=9(-3-h)^2+k\\67=9(-3-h)^2+(1-9(-1-h)^2)

And now, we just have to simplify.

First, from each of the square, factor out a negative 1:


67=9((-1)(h+3))^2+(1-9(((-1)(h+1))^2)

Power of a product property:


67=9((-1)^2(h+3)^2)+(1-9((-1)^2(h+1)^2))

The square of -1 is positive 1. Thus, we can ignore them:


67=9(h+3)^2+(1-9(h+1)^2)

Square them. Use the trinomial pattern:


67=9(h^2+6h+9)+(1-9(h^2+2h+1))

Distribute:


67=(9h^2+54h+81)+(1-9h^2-18h-9)

Combine like terms:


67=(9h^2-9h^2)+(54h-18h)+(81+1-9)

The first set cancels. Simplify the second and third:


67=36h+73

Subtract 73 from both sides. The right cancels:


67-73=36h+73-73\\36h=-6

Divide both sides by 36:


(36h)/36=(-6)/36\\h=-1/6

Therefore, h is -1/6.

Now, plug this back into the equation we isolated to solve for k:


k=1-9(-1-h)^2

First, remove the negative by simplifying:


k=1-9((-1)(h+1))^2\\k=1-9((-1)^2(h+1)^2)\\k=1-9(h+1)^2

Plug in -1/6 for h:


k=1-9(-(1)/(6)+1)^2

Add. Make 1 into 6/6:


k=1-9(-(1)/(6)+(6)/(6))^2\\ k=1-9((5)/(6))^2

Square:


k=1-9((25)/(36))

Multiply. Note that 36 is 9 times 4:


k=1-9((25)/(9\cdot4))\\ k=1-(25)/(4)

Convert 1 into 4/4 and subtract:


k=(4)/(4)-(25)/(4)\\ k=-(21)/(4)

So, the vertex is (-1/6, -21/4).

Now, plug everything back into the very original equation with 9 as a:


f(x)=a(x-h)^2+k\\f(x)=9(x+(1)/(6))^2-(21)/(4)

And this is our answer :)

User Sworded
by
6.6k points